A biopsychospiritual framework for the investigation of khushu’ - Jaffer, Usman; Che Mohd Nassir, Che Mohd Nasril; Abdul Razak, Abdul Latif; Abidin, Mohd Radhwan; Ahmad H.Osman, Rahmah; Ahmed, Mohamad Ayaaz (ResearchTrentz, 2022)
Khushu’ is a state that is required of every Muslim in prayer specifically and humans generally. It includes a state of utter humility with the Devine in an absorbed fashion in prayer and an overall approach to life out of prayer, the result being resilient human beings and a state of mindfulness, with an utmost respect for The Creator as well as creation. Not everyone achieves it. It has been attributed as a function of the “spiritual heart”. Thus, the physical heart as well as the brain will be primary regions of interest. Thus far it has onlybeen explored as a religious concept. A framework is thus needed to investigate the biopsychospiritual dimensions of this construct. A framework thus comprising of psychocardiological mechanisms, brain microvascular pulsatility, systamatic biomarkers and neuroimaging techniques such as fMRI and DTI and/or tractography that enable in vivo assessment of the spatial and temporal pattern of functional and structural changes was proposed. This framework can contribute to the elucidation of critical aspects in Khushu’, in terms of physiological regulation and modulation as well as brain remodelingin individuals contributing to the understanding of as well as applying Khushu’ for the betterment of individuals.